The fuzzy decision tree application to a power system problem - Lo K.L.; Abidin H.I.H.Z (2023)
This paper describes voltage collapse in power system networks and how it could lead to a collapse of the whole system. Discusses the effect of machine learning and artificial intelligence leading to new methods. Spotlight the fuzzy decision tree (FDT) method and its application to voltage collapse assessments. Concludes that FDT can identify and group data sets giving a new understanding of its application in voltage collapse analysis.